Species profiles life histories and environmental requirements of coastal fishes and invertebrates (North Atlantic)--American shad - Weiss-Glanz, Lori S. (U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.59)